Penerapan Kompres Hangat dan Tarik Nafas dalam Mengatasi Nyeri Akut Pasien Hipertensi - Wahyu Utami Mauliddia; Suci Khasanah; Asmat Burhan (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2022)
Pain conditions are very often complained of in hypertensive patients. Pain often occurs in the nape of the neck due to increased pressure on the walls of blood vessels around the neck, increased vascular pressure to the brain so that there is an emphasis on the neck muscle fibers. This study aims to describe the nursing care process and the use of a warm compress intervention combined with deep breathing relaxation techniques. The results showed that the patient was diagnosed with hypertension. The patient complained of dizziness and neck pain like being crushed by a heavy object, a scale of 5 due to stress and a lot of pressure. Pain occurs approximately 1 hour and always occurs on every wake. Blood pressure reached 190/100 mmHg, pulse 91 beats per minute, RR 20 beats per minute, and temperature 36.30C. The warm compress intervention combined with deep breathing was carried out for 3 days and was proven to be able to reduce the pain scale felt by hypertensive clients.